UNDERSTANDING NURSING HOME STAFF ATTITUDES TOWARDS DEATH AND DYING. (11th November 2018) - Bui, N; Halifax, E; Uy, E; Hunt, L; David, D; Lee, S J; Ritchie, C; Stephens, C
Abstract: Nearly 70% of nursing home (NH) residents are palliative care eligible, yet few receive formal palliative care (PC) outside of hospice. Little is known about NH staff PC knowledge, attitudes, skills, behaviors relating to death and dying. We administered the Attitudes Towards Death survey to 105 NH staff (49 CNAs, 33 nurses, 23 non-clinical staff) from 14 NHs. NH staff generally feel comfortable caring for the dying, however half believe EOL is a time of great suffering. Pain control (67%), loneliness(54%), and depression(50%) were the most important issues identified in caring for these patients, with ambivalence about possible dangers of strong pain medication and utility of feeding tubes at EOL. Top priorities identified for improving PC/EOL care included: greater family involvement (50%); education/training on pain control (48%) and management of other symptoms (33%); and use of a PC team (34%). Findings provide guidance on how best to target PC education/support.